Lipoprotein Heterogeneity Early in Pregnancy and Preterm Birth - Catov, Janet M.; Mackey, Rachel H.; Scifres, Christina M.; Bertolet, Marnie; Simhan, Hyagriv N. (American Journal of Perinatology, 2017)
Background The concentration and size of lipoprotein particles are associated with race, inflammation, and disease. When triglycerides are high, as in pregnancy, lipoprotein particle size may have physiologic importance beyond conventional lipid measurements. We considered that lipoprotein particles may be related to preterm birth (PTB) and explored race differences.Materials and Methods Samples were collected at 9 weeks' gestation (22 PTB [< 37 weeks]; 42 term births [≥ 37 weeks]). Lipids were assayed using standard techniques. Concentrations of high-density lipoprotein, low-density lipoprotein, and very low-density lipoprotein particles (HDL-P, LDL-P, and VLDL-P, respectively) and markers of systemic inflammation were quantified using nuclear magnetic resonance spectroscopy and related to PTB.Results Women with PTB had lower VLDL-P (− 10.66 nmol/L, p = 0.03) and higher systemic inflammation (+ 19.2 µmol/L, p = 0.02) compared with women with term births, independent of race, pre-pregnancy body mass index, and smoking. Black versus white women had lower VLDL-P and higher HDL cholesterol (both p < 0.05). Race-specific results indicated that large HDL-P and inflammation (glycoprotein B) were higher with PTB versus term birth among black women only.Conclusion Women with PTB had lower VLDL-P early in pregnancy, which may represent impaired lipid response. Black–white differences in the lipoprotein profile are similar to nonpregnant adults, but race-specific lipoprotein and inflammation associations with PTB warrant further study.
Keywords: inflammation; lipids; lipoproteins; pregnancy